Structural evolution and exhumation history of the Rhodope UHP-HP metamorphic province (Northern Greece) - KROHE, A.; MPOSKOS, E. (Bulletin of the Geological Society of Greece, 2001)
Middle/Early Alpine UHP-HP domain of the Rhodope (N'Greece) show pressures >3.6 Gpa. UHP-HP rocks have been emplaced in three major tectonic pulses: (i) At about 65->48 Ma the UHP Kimi Complex was exhumed at the surface representing the structurally uppermost UHP unit, (ii) Between > 42-30 Ma, the Sidironero, Kardamos and Kechros Complexes were exhumed underlying the Kimi Complex in the central and eastern Rhodope, respectively. They are characterized by HP-metamorphism (some parts by UHP-metamorphism), isothermal decompression and probably rapid exhumation. Exhumation tectonics involves deep level thrusting, synchronous high level extension, and successive post-thrusting extension. The post-thrusting Xanthi low angle normal detachment system extending over a distance of 100 km, from central Rhodope to eastern Rhodope, is interpreted to be responsible for a decrease in recent crustal thickness of about 20 km from central to eastern Rhodope. Lutetian (c. 48-43Ma) to Oligocene marine basins transgressed atop the Kimi Complex representing the upper plate of all detachment generations, (iii) The third exhumation pulse between 26 to 8 Ma, exhumed the Thasos/Pangeon metamorphic core complexes representing the structurally lowermost tectonic units of the Rhodope domain. Their exhumation occurred by displacements on the Miocene Strymon and Thasos detachment systems.